La Rev Burger, una empresa social y su proceso de internacionalización (2017)
In this monograph we analyze several fields related to the company La Rev Burger, among which are its internationalization process and its component as a social enterprise. Through the research and strategies used to date, it is possible to clarify which are the necessary parameters for such internationalization and if it is in the same conditions. Likewise, the characteristics of social enterprises are presented to determine if the Rev Burger is in a position to be a social enterprise. On the other hand, in terms of its internationalization process, it will be possible to differentiate which of the existing processes, is more in line with what the Rev Burger requires in order to determine what is the most appropriate for the company, in this case a family company, which intends to venture into the market with their vegetarian products, thus achieving a change in the eating habits of people.